1998
DOI: 10.4039/ent130337-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Against White Pine Weevil: Effects on Weevil Reproduction and Host Finding

Abstract: Feeding on leaders of resistant Sitka spruce trees, Picea sitchensis (Bong.) Carr., Led to ovarian regression in white pine weevils, Pissodes strobi Peck., that contained already mature eggs at the time of caging on leaders. Such feeding also led to inhibition or a virtual blockage of ovarian development in weevils that did not contain already mature eggs at the time of caging. Ovarian maturation in such weevils was restored by application of juvenile hormone to female weevils. Effects of three levels of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…They concluded that this rise in JH was suggestive of a role for JH in coordinating reproduction on an unpredictable resource. The white pine weevil, Pissodes strobi, has been found to have reduced ovarian development on a poor oviposition resource, a reduction that could be corrected by the topical application of JH (Sahota et al 1998). Sahota et al (1998) concluded that feeding on the resistant oviposition resource disrupts the normal function of the JH system by way of an antibiotic mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that this rise in JH was suggestive of a role for JH in coordinating reproduction on an unpredictable resource. The white pine weevil, Pissodes strobi, has been found to have reduced ovarian development on a poor oviposition resource, a reduction that could be corrected by the topical application of JH (Sahota et al 1998). Sahota et al (1998) concluded that feeding on the resistant oviposition resource disrupts the normal function of the JH system by way of an antibiotic mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The white pine weevil, Pissodes strobi, has been found to have reduced ovarian development on a poor oviposition resource, a reduction that could be corrected by the topical application of JH (Sahota et al 1998). Sahota et al (1998) concluded that feeding on the resistant oviposition resource disrupts the normal function of the JH system by way of an antibiotic mechanism of resistance. However, if P. strobi requires host encounter to stimulate the function of the JH system in the same way that burying beetles do, then it is possible that they are also a species where simple host quality and availability is driving the reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…One example of such antibiosis was observed by Sahota et al (1998) who found that white pine weevils experienced ovarian regression when forced to feed on only resistant Sitka spruce. For C. lapathi, oviposition deterrence in resistant clones was most pronounced when oviposition levels in general were low, indicating that weevils were probably already experiencing suboptimal conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Adult female weevils may also feed on spruce foliage before selecting trees for ovipositing (Silver 1968), so the potential exists for antibiosis by the foliar alkaloids as well. Resistance appears to result, at least in part, from unidentiÞed water-soluble constituents of spruce bark that cause hormonal changes which inhibit egg production in female weevils (Leal et al 1997;Sahota et al 1998Sahota et al , 2001. We have found the piperidine alkaloids to be water-soluble (unpublished data) and constitutive in nature (Gerson and Kelsey 1998).…”
mentioning
confidence: 84%